Foundational Java Key Elements and Practical Programming - Parsons, David; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Java is now well-established as one of the world’s major programming languages, used in everything from desktop applications to web-hosted applications and enterprise systems, and embedded in devices such as mobile phones and Blu-ray players. Foundational Java: Key Elements and Practical Programming presents a detailed guide to the core features of Java – and some more recent innovations – enabling the reader to build their skills and confidence though tried-and-trusted stages, supported by exercises that reinforce the key learning points. All of the most useful and commonly applied Java syntax and libraries are introduced, along with many example programs that can provide the basis for more substantial applications. Use of the Eclipse Integrated Development Environment (IDE) and the JUnit testing framework is integral to the book, although to ensure that skills are not confined to one environment the fundamentals of the Java compiler and run time are also explained. Additionally, coverage of the Ant tool will equip the reader with the skills to automatically build, test and deploy applications independent of an IDE. Topics and features: Presents the most up-to-date information on Java, including Java 7 Examines the key theme of unit testing, introducing the JUnit 4 testing framework Describes the Eclipse IDE, and also explains how Java can be run from the command line Includes coverage of the Ant build tool Contains numerous code examples and exercises throughout Provides downloadable source code, self-test questions, and PowerPoint slides at an associated website This hands-on, classroom-tested textbook/reference is ideal for undergraduate students on introductory and intermediate courses on programming with Java. Professional software developers will also find this an excellent self-study guide/refresher on the topic.
The Java Story -- Compiling and Running Java Programs -- Data Types, Arithmetic and Arrays -- Control Structures -- Creating Objects -- Creating Domain Classes -- Objects Working Together: Association, Aggregation and Composition -- Inheritance, Polymorphism and Interfaces -- Exception handling -- Unit Testing With JUnit -- Exploring the Java Libraries -- The Collections Framework and Generics -- Input and Output Streams -- Automatic Building and Testing with Ant -- Java and the Database (JDBC) -- Multithreading -- Building GUIs with the JFC Swing Library -- Event Driven Programming -- Dialogs and Menus, Models and Views -- Java Web Start and Applets.
Keywords: Programming languages (Electronic computers).; Computer programming; Software engineering; Programming Languages, Compilers, Interpreters; Programming Techniques; Software Engineering